2018
DOI: 10.1080/23745118.2018.1545181
|View full text |Cite
|
Sign up to set email alerts
|

Russia and the question of world order

Abstract: There is broad agreement among commentators and analysts that Russia seeks to undermine the US-led liberal international order. At the same time, there is considerable disagreement over the nature and extent of the challenge Moscow poses, the underlying drivers of Russian revisionism, and how the West should respond. In this article, we argue that it is possible to distinguish between three major perspectives. In brief, the first suggests that Russia is a 'revanchist power' that seeks to overturn the very foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Others scholars, on the contrary, emphasized that Moscow nationalism and territorial expansionism is a real threat to the liberal international order and suggested that USA and EU should resist Russian revisionism through a mix of a containment and rollback. In short, they should reinforce diplomatic efforts to isolate Moscow; impose more severe sanctions; increase NATO military deployments in Eastern Europe and the Baltic states; provide military support to Georgia and Ukraine (Götz, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Others scholars, on the contrary, emphasized that Moscow nationalism and territorial expansionism is a real threat to the liberal international order and suggested that USA and EU should resist Russian revisionism through a mix of a containment and rollback. In short, they should reinforce diplomatic efforts to isolate Moscow; impose more severe sanctions; increase NATO military deployments in Eastern Europe and the Baltic states; provide military support to Georgia and Ukraine (Götz, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…51 argues that the motivating force behind these tactics is the imperative of regime survival. 52 Focusing on an external threat helps to invoke patriotism and benefits those currently in power, who want to maintain the status quo. Russia has many of the trademarks we expect to see that explain why Russia is imagining the Arctic as a zone of conflict including both growing social unrest as well as rhetoric geared towards a domestic audience that encourages a focus on conflict outside the state.…”
Section: Russian Domestic Politics Since 2016mentioning
confidence: 99%
“…Clunan, 2018;Hill, 2018;Jankovski, 2017;Kanet, 2018;Morozov, 2015;Radin & Reach, 2017;Romanova, 2018;Sakwa, 2017;Voskressenski, 2016). At the risk of oversimplification, one can distinguish between three positions in the ongoing debate: for some, Russia is a revolutionary or revisionist power intent upon destroying the present order; for others, it is an anti-reformist conservative force seeking to restore order; and for still others, it lies somewhere in between and seeks only minor adjustments (for an overview, see the introductory article by Götz and Merlen, 2018).…”
Section: Introductionmentioning
confidence: 99%